The effect of slope curvature in rock mass shear strength derivations for stability modelling of foliated rock masses - Narendranathan, S; Thomas, RDH; Neilsen, JM (Slope Stability 2013: Proceedings of the 2013 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2013)
In open pits the instability mechanisms are multifaceted involving; shearing along or over the asperities of the defect surface and/or block rotation at very low normal stresses. At higher degrees of confinement, shearing along or through asperities and block rotation including rock mass failure due to intact rock breakage can occur. It is common to have pit designs with varying profiles resulting in concave, straight and convex geometries. This difference in wall geometry would result in varying magnitudes of effective shear strength being mobilised. The contribution of the lateral confinement to the degree of shear strength mobilised is often overlooked in design. In this paper a case study will be presented, which compares the different slope performance outcomes within similar geotechnical conditions with the only variant being the slope geometry and the influence of lateral confinement. An algorithm is developed, based on observations from this site case study, linking the concavity of a slope face to the degree of (extra) shear strength mobilised. It is the authors intent that this algorithm can be used in a similar manner to which highway engineers use ‘curve-speed models’ to determine safe approach speeds for corners given a particular road curvature, (in our case pit slope concavity) and approach speed (rock mass characteristics). This relationship has been implemented for forward analyses at the mine in question; however the authors acknowledge that further work needs to be undertaken so as to ensure the validity of the relationship for generalised application.